Assessment of in vitro efficacy for common surface disinfectants and antiseptics against Tritrichomonas foetus trophozoites - Martin, Katy A.; Kovach, Kristofer; Moscoso, Erica; Carreiro, Elizabeth; Jesudoss Chelladurai, Jeba R. J.; Brewer, Matthew T. (Frontiers in Veterinary Science, 2023)
The protozoan Tritrichomonas foetus causes early embryonic death in cattle, there are no legal options for treating this parasite in the United States, and there are few developed protocols for cleaning veterinary and obstetrical equipment that may have been contaminated with trophozoites. In this study, we evaluated bleach, ethanol, acetic acid, chlorhexidine gluconate, and hydrogen peroxide solutions for the ability to kill trophozoites in vitro. Our findings suggested that ethanol and bleach could adequately disinfect tools and equipment.Acetic acid, chlorhexidine, and hydrogen peroxide had applications as surface disinfectants in addition to potential as local topical treatments due to their past uses in veterinary theriogenology. Chlorhexidine gluconate demonstrated trophocidal effects by damaging parasite cell membranes and had the lowest effective concentration 50 (EC50) of any compound tested and was in the micromolar range. These findings, in conjunction with accepted clinical uses of chlorhexidine gluconate suggest that this is a convenient agent for disinfecting equipment. In addition, topical use of chlorhexidine is relatively common, setting the stage for further investigation of this compound as a topical therapeutic option for bovine trichomonosis.